THE EFFECT OF SELF-REGULATED STRATEGY DEVELOPMENT (SRSD) ON STUDENTS' WRITING MOTIVATION IN RECOUNT TEXT - juliantina - -; Seget Tartiyoso; Masita Ranti (Jurnal Serunai Bahasa Inggris, 2022)
The study deals with an experimental research design which seeks for the effect of Self-Regulated Strategy Development (SRSD) on students’ writing motivation in recount text. 52 students at the tenth grade students of MAS Al Washliyah 29 Binjai on the first semester in academic year 2021/2022 were taken as the samples of the study. The research instrument used by the writer in collecting data was post-test. It was conducted in order to know the flexibility on students’ writing ability material between learning process with small group discussion and learning process through Self-Regulated Strategy Development (SRSD). The final data then was analyzed by using Paired-Samples T Test analysis shown that the significance (sig) 2-tailed value 0.000000 was lower than the significance level (0.05) and determined that coefficient of tcounted was 24.787 signifying higher than the ttable coefficient (2.05954) with significance level (α) = 0.025 (2-tailed) with degree of freedom (df) = 25. This means that there is a significant effect of Self-Regulated Strategy Development (SRSD) on students’ writing motivation in recount text at the tenth-grade students of MAS Al Washliyah 29 Binjai in academic year of 2021/2022. Therefore, Ha was accepted and H0 was rejected.